Delayed Staged Hepatectomy for Metastatic Colorectal Cancer: A Single Case Report - Tendean, Michael; Paparang, Steven; Tjandra, Ferdinand; Mambu, Toar; Panelewen, Jimmy; Salem, Billy (Universitas Sam Ratulangi, 2025)
Abstract: Liver metastases are common in patients with colorectal cancer; almost 70% will develop liver metastases during the course. The recommended treatment for colorectal liver metastasis (CRLM) is multidisciplinary, including liver resection and chemotherapy. We reported a 52-year-old female with stage 3B distal third rectal adenocarcinoma which eight months earlier underwent Mile’s procedure plus total mesorectal excision (TME) followed by adjuvant radiotherapy (50gy). During surveillance, liver metastases was found at segments 4B-5. A delayed anatomical staged hepatectomy segments 4B-5 was performed. Intraoperative USG findings suggested liver metastases at segments 7, 8, and 3, and non-anatomical liver resection was performed in accordance with parenchymal liver sparing principles. No post-hepatectomy liver failure (PHLF) was detected, but billoma occured at 1-month post hepatectomy. USG guided percutaneous drainage was performed to resolve the billoma. Colorectal metastasis (CRLM) was detected at six months post-hepatectomy, and the patient underwent adjuvant chemotherapy with improvement in survival rate. In conclusion, delayed staged hepatectomy for CRLM is a safe and beneficial procedure, though there is still no guideline regarding the sequence of resection. Keywords: hepatectomy; colorectal metastasis; billoma; colorectal cancer